Normal left ventricular myocardial thickness for middle-aged and older subjects with steady-state free precession cardiac magnetic resonance: the multi-ethnic study of atherosclerosis - Kawel, Nadine; Turkbey, Evrim B; Carr, J Jeffrey; Eng, John; Gomes, Antoinette S; Hundley, W Gregory; Johnson, Craig; Masri, Sofia C; Prince, Martin R; van der Geest, Rob J; Lima, João A C; Bluemke, David A (Circulation. Cardiovascular imaging, 2012)
Increased left ventricular myocardial thickness (LVMT) is a feature of several cardiac diseases. The purpose of this study was to establish standard reference values of normal LVMT with cardiac magnetic resonance and to assess variation with image acquisition plane, demographics, and left ventricular function. End-diastolic LVMT was measured on cardiac magnetic resonance steady-state free precession cine long and short axis images in 300 consecutive participants free of cardiac disease (169 women; 65.6 ± 8.5 years) of the Multi-Ethnic Study of Atherosclerosis cohort. Mean LVMT on short axis images at the mid-cavity level was 5.3 ± 0.9 mm and 6.3 ± 1.1 mm for women and men, respectively. The average of the maximum LVMT at the mid-cavity for women/men was 7/9 mm (long axis) and 7/8 mm (short axis). Mean LVMT was positively associated with weight (0.02 mm/kg; P=0.01) and body surface area (1.1 mm/m(2); P<0.001). No relationship was found between mean LVMT and age or height. Greater mean LVMT was associated with lower left ventricular end-diastolic volume (0.01 mm/mL; P<0.01), a lower left ventricular end-systolic volume (-0.01 mm/mL; P=0.01), and lower left ventricular stroke volume (-0.01 mm/mL; P<0.05). LVMT measured on long axis images at the basal and mid-cavity level were slightly greater (by 6% and 10%, respectively) than measurements obtained on short axis images; apical LVMT values on long axis images were 20% less than those on short axis images. Normal values for wall thickness are provided for middle-aged and older subjects. Normal LVMT is lower for women than men. Observed values vary depending on the imaging plane for measurement.